Morphology and Magneto‐Transport in Exfoliated Graphene on Ultrathin Crystalline β‐Si3N4(0001)/Si(111). Issue 11 (19th April 2020) - Salimian, Sedighe; Xiang, Shaohua; Colonna, Stefano; Ronci, Fabio; Fosca, Marco; Rossella, Francesco; Beltram, Fabio; Flammini, Roberto; Heun, Stefan
Abstract: This work reports the first experimental study of graphene transferred on β‐Si3 N4 (0001)/Si(111). A comprehensive quantitative understanding of the physics of ultrathin Si3 N4 as a gate dielectric for graphene‐based devices is provided. The Si3 N4 film is grown on Si(111) under ultra‐high vacuum (UHV) conditions and investigated by scanning tunneling microscopy (STM). Subsequently, a graphene flake is deposited on top of it by a polymer‐based transfer technique, and a Hall bar device is fabricated from the graphene flake. STM is employed again to study the graphene flake under UHV conditions after device fabrication and shows that the surface quality is preserved. Electrical transport measurements, carried out at low temperature in magnetic field, reveal back gate modulation of carrier density in the graphene channel and show the occurrence of weak localization. Under these experimental conditions, no leakage current between back gate and graphene channel is detected. Abstract : Graphene is exfoliated on ultrathin crystalline β‐Si3 N4 (0001) on Si(111) and processed into a field‐effect transistor. Scanning tunneling microscopy demonstrates the high surface quality of the Si3 N4 and the graphene film. The graphene channel can be modulated in a wide range of back gate voltages without leakage through the ultrathin gate dielectric at 4.2 K.